Paciente femenino de 39 años de edad con diabetes gestacional y sobrepeso. - Arias Zambrano, Lady Diana (2021)
The present study deals with a 39-year-old female patient with gestational diabetes and overweight, with 20 weeks of gestation. Taking into account that it is a high-risk pregnancy due to gestational diabetes and being overweight, there are various complications, both in the mother and in the child. During the course of the development of the clinical case, the nutritional status of the patient was determined through anthropometric, biochemical, clinical and dietary methods, giving as initial diagnosis preconception BMI overweight and gestational diabetes. Given this, a diet plan is prescribed, according to the pathophysiological conditions and nutritional needs of the patient. Nutritional follow-up of one month is given and the general objective of the present study was achieved.